Institution of the People's Consultative Assembly of the Republic of Indonesia After the Amendments to the 1945 Constitution in State Administration - Firman Freaddy Busroh (International Journal of Artificial Intelligence Research, 2022)
Four times, in 1999, 2000, 2001, and 2002, amendments to the 1945 Constitution of the Republic of Indonesia (1945 Constitution of the Republic of Indonesia) were made. With the amendments to the 1945 Constitution of the Republic of Indonesia, the Indonesian constitutional system, particularly the institution of the MPR-RI, has undergone substantial alterations. Based on the 1945 Constitution and the Fourth Amendment, the Indonesian parliament might be composed of three chambers or institutions simultaneously. This is justifiable due to the MPR's establishment as a separate organization from the DPR and DPD. The 1945 Constitution continues to grant the MPR independent authority from the DPR and DPD. The purpose of this study is to determine the existence of the MPR after the 1945 Constitution was amended in accordance with the Indonesian Constitution. This study employs a qualitative approach and descriptive methodologies. In our constitutional system, the Indonesian legislative institution does not correspond to the concept of bicameralism as conceptualized by experts; rather, it adheres to the concept of tricameralism. This is proven by the existence of the MPR, DPR, and DPD, which each possess equal authority but are still superior to one another. Due of this, some refer to the Indonesian parliamentary system as a half-hearted tricameral